Literature Review: The Effect of Square Stepping Exercise on Dynamic Balance Levels in Reducing The Risk of Falling in the Elderly - Novianti Purwa Bestari; Nungki Marlian Yuliadarwati (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2022)
Background: Balance disorders are one of the problems that can cause the elderly to fall and experience a high risk of disability if not treated immediately. This problem occurs because of changes and setbacks in the body's system which results in a decrease in muscle strength and muscle contraction. Square stepping exercise (SSE) is one of the exercises that can help improve balance and cognitive disorders in the elderly because they have multi-directional movement patterns. Purpose: To determine the effect of Square stepping exercise (SSE) on the level of dynamic balance in reducing the risk of falls in the elderly. Method: The design of this study uses a literature review, namely by identifying several articles and scientific journals based on the inclusion and exclusion criteria of the sample, then they will be analyzed to obtain more accurate information. Articles and scientific journals were obtained using a database in the form of Google Scholar, PubMed, IJSR with the criteria for the 2015-2020 publishing year according to the theme in the title. Result: After analyzing articles and international scientific journals, it was found that the square stepping exercise (SSE) was mostly very effective in improving dynamic balance and reducing the risk of falling in the elderly. Conclusion: Based on scientific articles that have been identified and analyzed, there is an effect on giving Square Stepping Exercise on the level of dynamic balance in reducing the risk of falling in the elderly.